Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

3 (x- 4) = 2 (x+1)

Justification reason


Sagot :

Solution

=14

Step-by-step explanation:

3x-12=2x+2

3x-12=2x+23x-2x-12=2

3x-12=2x+23x-2x-12=2x=12+2

3x-12=2x+23x-2x-12=2x=12+2x=14